Gender equality and local culture in Northernmost Sweden (Tornedalen Area) : women’s views of men - Juntti-Henriksson, Ann-Kristin (Luleå tekniska universitet, Medier ljudteknik och upplevelseproduktion och teater, 2010)
Godkänd; 2011; 20110221 (andbra)